A streamlined workflow to study direct photodegradation kinetic and transformation products for persistence assessment of a fragrance ingredient in natural waters. Issue 10 (7th October 2019) - Lin, Jianming; Apell, Jennifer N.; McNeill, Kristopher; Emberger, Matthew; Ciraulo, Valerie; Gimeno, Sylvia
Abstract : A streamlined workflow was developed to generate relevant, reliable and transparent data on direct photodegradation kinetic and transformation products for environmental persistence assessment of fragrance chemicals for regulatory compliance. Abstract : Photodegradation can be an important abiotic degradation process to consider for the fate and persistence assessment of chemical substances in the environment. In this work, using a fragrance ingredient (FI, ( E )-4-(2, 2, 3, 6-tetramethylcyclohexyl)but-3-en-2-one) as an example, we developed a streamlined workflow to investigate direct photodegradation of chemicals in the aquatic environment, including laboratory investigation of kinetics and transformation products and estimation of its aquatic environmental half-lives. Direct photodegradation was determined to be the dominant photodegradation process for FI with a quantum yield of 0.25, which was supported by photodegradation experiments conducted in natural sunlight. Accounting for light attenuation by dissolved organic matter in natural waters of different depths resulted in aquatic half-lives of <31 days even at polar latitudes. Photoisomerization was shown to be a major photodegradation pathway along with the formation and subsequent degradation of constitutional isomers and photooxidation products. These results contributed to FI being assessed as non-persistent in the environment.